PREVENTION OF CORRUPTION IN THE VILLAGE GOVERNANCE BASED ON DEMOCRATIC GOVERNANCE PERSPECTIVE - Wanusmawatie, Ike (FIA UB, 2015)
Prevention Of Corruption In The Village Governance Based On Democratic Governance Perspective. This study describes and analyzes the phenomena of corruption in village government especially on village official recruitment. Methode of this study is library research. One of the result of this study showed there are three mechanisms in the recruitment or appointment of the village board. Ineachcontaining five perspective corruption to strengthen Cheema (2005:52) concept. The prevention of corruption in village governance can be achieved through the practice of administrative reforms that became part of the reform by using institutional governance model. It can be effectively carried out if first, supervision done by supra government of village and third parties, second, The use of local wisdom, and religious values as well as the provision of civic education are expected to form the moral integrity and responsibilityof village apparaturs. In the future, this study is important as input not only to prevent corruption but to improve of Â village governance performance.